2019
DOI: 10.5377/nexo.v32i02.9263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different parameters of heterogeneous dams on safety factor using the neural network. Case study: Marvan dam

Abstract: The drainage system is used to guide the flow of water in the earth dams. Construction of drainage in the dam body to collect and direct the drainage formed in the dam body to keep the slope dry and prevent the increase of pore water pressure in the body. One of the main goals of the designers is to find the minimum factor of safety and, consequently, reduce the cost of construction. In this study, the Marvak dam is modeled with the actual characteristics of the materials in the Geostudio software, and with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
1
0
4
Order By: Relevance
“…La función logística (LOGSIG) no tuvo resultados (0% de aciertos) por encima del 95%. Para el caso analizado, se aprecia un elevado coeficiente de correlación obtenido para un número reducido de neuronas ocultas, lo que contrasta con los planteado por diversos autores que han abordado el tema con anterioridad, como (Beiranvand et al, 2019;Costa, 2016;Montoya, 2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…La función logística (LOGSIG) no tuvo resultados (0% de aciertos) por encima del 95%. Para el caso analizado, se aprecia un elevado coeficiente de correlación obtenido para un número reducido de neuronas ocultas, lo que contrasta con los planteado por diversos autores que han abordado el tema con anterioridad, como (Beiranvand et al, 2019;Costa, 2016;Montoya, 2018).…”
Section: Resultsunclassified
“…Por otro lado, (Montoya, 2018) emplea la función de Levenberg-Marquardt obteniendo para suelos arcillosos un coeficiente de correlación R 2 de 83,2%. (Beiranvand, Mohammadzadeh, & Komasi, 2019) emplean la función de Regularización Bayesiana obteniendo un coeficiente de correlación R 2 de 99%, sin embargo, utilizan 25 neuronas en la primera capa oculta. (Gomes, 2016) utiliza seis modelos de redes neuronales con 20 y 25 neuronas en la primera capa oculta en todos los casos, obteniendo coeficientes de correlación R 2 entre 83% y 90%.…”
Section: Introductionunclassified
“…Para el caso analizado, se aprecia un elevado coeficiente de correlación obtenido para un número reducido de neuronas ocultas, lo que contrasta con los planteado por diversos autores que han abordado el tema con anterioridad, como (Beiranvand et al, 2019;Costa, 2016;Montoya, 2018). A partir de los resultados obtenidos, en ninguno de los casos analizados, cuando la función de activación de la segunda capa oculta es la función logística (LOGSIG) se obtuvieron errores por debajo del 5%.…”
Section: Figura 6 Modelo Implementado Con La Caja De Herramientas Para Redes Neuronales En Matlab ®unclassified
“…Año 12 N° 32, 2021 Isaida Flores Berenguer et al /// Evaluación de la estabilidad de taludes en presas de tierra … 261-283 DOI: http://dx.doi.org/10.46925//rdluz.32.17 264mediante la función tangente hiperbólica con 10 neuronas en la primera capa oculta y evalúa además sólo la función sigmoidea. Por otro lado,(Montoya, 2018) emplea la función de Levenberg-Marquardt obteniendo para suelos arcillosos un coeficiente de correlación R 2 de 83,2% (Beiranvand, Mohammadzadeh, & Komasi, 2019(Gomes, 2016).…”
unclassified
“…Some earth dam failures due to sudden drawdown such as (Pilarcitos Dam, south of San Francisco), and (Walter Boudin Dam in Alabama) have been listed in (Duncan, et al, 1990), and (Berilgen, 2007). Beiranvand, et al, (2019) examined the effect of internal friction angle and side slope ratio on the stability of a heterogeneous dam, based on the results, the researchers concluded that the angle of internal friction and side slope ratio has a considerable effect on the stability of the dam. Berilgen, (2017) emphasized that the stability of the submerged slopes during sudden drawdown depends on how fast the water dissipates.…”
Section: Introductionmentioning
confidence: 99%